Vladimír Helfert, zakladatel Hudebního archivu Moravského zemského muzea - Ondřej Pivoda (Musicologica Brunensia, 2016)
A foundation of the Music Archive of the Moravian Museum is connected with a relocation of Vladimír Helfert to Brno in 1919. Vladimír Helfert's idea to establish a modern music archive could realize due to cooperation with Vladimir's brother Jaroslav who worked as a secretary of the museum and since 1923 as its director. A development of the archive was initiated by acquiring a precious music collection from the Strážnice castle. Efforts of the Helfert brothers crossed with the endeavour of the Ministry of Education and National Culture to ensure a preservation of historic monuments which were endangered by potential export to Austria, Hungary etc. after the constitution of the Czechoslovakia in 1918. For that reason it was necessary to make quickly a register of those monuments. A base for creating a register and for subsequent preservation of the monuments of music was established by the Council of the Music Archive of the Moravian Museum in 1920. It consisted of the music conservators nominated for the Moravia and Silesia region by the Ministry of Education and National Culture. Vladimír Helfert was appointed as the Councils secretary. Activities of the Council consisted in preserving monuments of music, in creating its register and in collecting of the monuments in order to create a music archive. A proposal of the statutes of the Central Council for Preservation of Monuments of Music in the Czechoslovak Republic was a collective work by Vladimír and Jaroslav Helfert. In the statutes they divided a scope of authority amongst the work groups in Prague, Brno and Bratislava and included i.a. a plan on founding the State Music Archives and Museums in Prague and Bratislava. But the activities of Vladimír Helfert were primarily focused on organization of the Music Archive in Brno. He set down the principles of cataloguing and segmentation of the music collection of the archive and in cooperation with his first colleagues, the musicologists Karel Vetterl and Jan Racek, he created a solid basis for the development of the institution. Thanks to Vladimír Helfert the Music Archive of the Moravian Museum ranked soon among the most important and the most modern institutions of its kind in Europe.